ANALISIS YURIDIS TERHADAP IMPLEMENTASI UNDANG-UNDANG DASAR 1945 DALAM SISTEM HUKUM INDONESIA - Frengki Saputra (INTELIGENSIA MEDIA, 2026)
The 1945 Constitution of the Republic of Indonesia serves as the supreme law and the fundamental basis for state governance as well as the primary source of law within the Indonesian legal system. This study aims to provide a juridical analysis of the implementation of the 1945 Constitution in the Indonesian legal system and to examine its implications for the principles of the rule of law, constitutional supremacy, and the protection of human rights. This research employs a normative legal research method using statutory and conceptual approaches. Data were collected through library research by examining primary, secondary, and tertiary legal materials, which were analyzed qualitatively using a descriptive-analytical juridical method. The findings indicate that, normatively, the implementation of the 1945 Constitution has reflected the principles of the rule of law and constitutional supremacy, particularly through legislative processes, constitutional review by the Constitutional Court, and guarantees of human rights protection. However, in practice, several challenges remain, including weak law enforcement, non-compliance with constitutional provisions, and the potential abuse of power, which hinder the effective implementation of the Constitution. Therefore, strengthening legal awareness, institutional reform, and enhancing the effectiveness of law enforcement are essential to ensure that the 1945 Constitution is implemented consistently, fairly, and sustainably within the Indonesian legal system